Analysis of early-age cracking in thin steam-cured precast concrete elements - Gino, Karlo Garcia (Animo Repository, 2013)
Early-age cracking occurs when the early tensile strength capacity of the concrete is exceeded by the tensile thermal stresses during the hydration process. This is the case observed in a precast fabrication yard where 225mm thick sections are being produced. Although the cracks are within allowable limits, treatment following acceptable methods on site is made as part of the quality control procedure and this affects time and cost in production. This study aims to look into the probable causes of early-age cracking through theoretical analysis following CIRIA C660 and through computational analysis using MIDAS/Civil. The analysis was focused on the zone where the actual crack was observed. Both analyses were consistent in predicting the occurrence of early-age cracking. A parametric analysis is added on this study to see how different parameters influence the prediction of early-age cracking. Analysis was performed on the temperature, the curing process, the formwork, and the aggregate selection. The parametric analysis was carried out using CIRIA C660 and MIDAS/Civil. Parametric analysis show that temperature, curing process and aggregate selection have an influence in the prediction of early-age cracking, while formwork-type selection does not for this particular precast concrete section. An idealized scenario was then formed to determine, theoretically, how early-age cracking can be eliminated.